Retreatment with brentuximab vedotin for discordant peripheral T-cell lymphomas - Gen Hasegawa; Noriharu Nakagawa; Yoshimichi Ueda; Masahide Yamazaki (Leukemia Research Reports)
Brentuximab vedotin (BV) has demonstrated efficacy against CD30+ peripheral T-cell lymphoma (PTCL). We herein report a case of CD30+ peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS) that emerged one month after completing BV, cyclophosphamide, doxorubicin, and prednisone (BV-CHP) therapy for anaplastic large cell lymphoma (ALCL) and responded to retreatment with BV monotherapy. This case suggests that CD30+ PTCL emerging shortly after BV-CHP therapy may respond to retreatment with BV monotherapy, even if the phenotype differs from the initial diagnosis.